Obesity as a significant risk factor for endometrial cancer - Suskic, Amer; Suskic, Sanela Halilovic; Opric, Dejan; Maksimovic, Sinisa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Endometrial cancer is the most developed countries the most common invasive neoplasms of the female reproductive system. The most frequently mentioned risk factors, which are associated with the occurrence of endometrial cancer are obesity, infertility, high blood pressure, diabetes, liver disease, hormone-active tumors of the ovary, and the use of external estrogen. Methods: This paper deals with data of the patients treated for endometrial carcinoma in Public Hospitals in Travnik, gynecological department in the period from 01 January 2007 to 01 January 2013 the sample consisted of 90 women with endometrial carcinoma, with ages ranging from 42 to 90 years (mean of 64 years). Results: 65 cases (73%) were of endometrioid and 25 (27%) nonendometrioid carcinoma. Obesity is an important risk factor for endometrial carcinoma, in our sample of 90 patients most of the patients was obese, and this risk factor was statistically processed and presented. Endometrioid carcinoma had 16 (45%) patients with a BMI <30 kg / m2, and the Non-endometrioid carcinoma had 20 (55%) patients. 38 (70%) patients with a BMI> 30 kg / m2 had endometrioid carcinoma, and 16 patients (30%) had Non-endometrioid carcinoma. Conclusions: Obesity is the strongest risk factor for the development of endometrial cancer due to the mechanism of increased exposure to non-opposed estrogen. Consequently, the link between obesity and endometrial cancer is stronger in cases of tumor type 1, typical estrogen-dependent tumors.